The Role of Traditional Chinese Medicine and Chinese Pharmacopoeia in the Evaluation and Treatment of COVID-19 - Gasmi, Amin; Noor, Sadaf; Dadar, Maryam; Semenova, Yuliya; Menzel, Alain; Gasmi Benahmed, Asma; Bjørklund, Geir (Current Pharmaceutical Design, 2024)
The epidemic prompted by COVID-19 continues to spread, causing a great risk to the general population's safety and health. There are still no drugs capable of curing it. Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) are the two other diseases caused by coronaviruses. Traditional Chinese Medicine (TCM) showed benefits in treating SARS and MERS by preventing the disease early, substantially mitigating symptoms, shortening the treatment period, and minimizing risks and adverse reactions caused by hormone therapy. Although several vaccines have been developed and are being used for the treatment of COVID-19, existing vaccines cannot provide complete protection against the virus due to the rapid evolution and mutation of the virus, as mutated viral epitopes evade the vaccine’s target and decrease the efficacy of vaccines. Thus, there is a need to develop alternative options. TCM has demonstrated positive effects in the treatment of COVID-19. Previous research studies on TCM showed broad-spectrum antiviral activity, offering a range of possibilities for their potential use against COVID-19. This study shed some light on common TCM used for SARS and MERS outbreaks and their effective use for COVID-19 management. This study provides new insights into COVID-19 drug discovery.
Keywords: COVID-19